Discovery of Synuchus congruus (Morawitz, 1862) (Coleoptera, Carabidae, Sphodrini) in Europe - Mikalai Kazulka; Alexander Anichtchenko; Oleg Aleksandrowicz (ZooKeys)
The eastern Palearctic carabid beetle Synuchus congruus (Morawitz, 1862) is recorded from Belarus, Latvia, and Poland. Images of habitus, morphological features, and aedeagi, as well as an updated key to the Synuchus species of Europe, are provided.